2017
DOI: 10.12989/acc.2017.5.1.31
|View full text |Cite
|
Sign up to set email alerts
|

Effect of metakaolin on the properties of conventional and self compacting concrete

Abstract: Supplementary cementitious materials (SCM) have turned out to be a vital portion of extraordinary strength and performance concrete. Metakaolin (MK) is one of SCM material is acquired by calcinations of kaolinite. Universally utilised as pozzolanic material in concrete to enhance mechanical and durability properties. This study investigates the fresh and hardened properties of conventional concrete (CC) and self compacting concrete (SCC) by partially replacing cement with MK in diverse percentages. In CC and S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(21 citation statements)
references
References 20 publications
(27 reference statements)
3
17
1
Order By: Relevance
“…no blocking or segregation phenomenon were found in the mixes at the time of the test execution. these results are similar to the results study [25]. From the previous works on fresh test of blended SCHPC, it can be observed that the replacement of CKC or NL, from the cement, rises in water demand because of their fineness and reactivity with cement [24,28].…”
Section: Fresh Examination Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…no blocking or segregation phenomenon were found in the mixes at the time of the test execution. these results are similar to the results study [25]. From the previous works on fresh test of blended SCHPC, it can be observed that the replacement of CKC or NL, from the cement, rises in water demand because of their fineness and reactivity with cement [24,28].…”
Section: Fresh Examination Resultssupporting
confidence: 90%
“…Besides, the large surface area of calcined kaolin clay leads to an increase in a reaction as well. these results are in agreement with the previous work [22,25].…”
Section: Compressive Strengthsupporting
confidence: 94%
See 2 more Smart Citations
“…Lastly, the replacement of OPC by the binary admixtures (FA+MK) was varied as given in Table 2 [17]. With inclusion of MK in SCC water absorption values decreases with higher percentage of replacement [18].…”
Section: Water Absorption Testmentioning
confidence: 99%